Macro-costing of the use of bortezomib in the treatment of multiple myeloma from the perspective of the SUS - Andrades Fiorini Monteiro Novo, Mariana; Oliveira Cantadori, Lucas; Dezen Gaiolla, Rafael; de Oliveira Silva, Lukas Fernando; dos Santos Nunes-Nogueira, Vania (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: Bortezomib is one of the most widely used medicines in the treatment of multiple myeloma (MM). Objective: To conduct a macro-costing study of the use of bortezomib in the treatment of MM from the perspective of the Unified Health System (SUS). Methods: Direct costs related to the acquisition of bortezomib were considered. The annual incidence of MM cases and the estimated number of patients undergoing treatment were calculated using data from the Department of Information Technology of the Unified Health System (DATASUS). The cost of bortezomib was obtained from the Health Price Database (BPS). The approximate cost per patient was compared to the amount reimbursed by the Outpatient Procedure Authorization (APAC). Two treatment possibilities were considered: 9 cycles, used for patients who are candidates for autologous hematopoietic stem cell transplantation (ASCT) (30% of the population); and 12 cycles used for patients who are not candidates for ASCT (70%). Results: Considering 1.3mg/m2 and 1.5mg/m2, and a dose wastage of 10%, the cost per patient in 9 cycles was R17,678.30 and R18,023.64, respectively. For 12 cycles the cost was R23,569.94 for a dose of 1.3mg/m2 and R24,030.39 for a dose of 1.5mg/m2. According to the current APAC value, which is R5,224.65, the total amount paid for the treatment of 9 cycles is R47,021.85 and for 12 cycles it is R62,695.80. Discussion and Conclusion: The average cost of treatment with bortezomib per patient was R22,100.59, and the amount reimbursed by APAC was R57,993.62. However, it is emphasized that only the direct costs of acquiring bortezomib were computed.